- TANGGUNG JAWAB PELAKU USAHA ATAS PRODUK PANGAN TIDAK LAYAK JUAL : - - Anggi Suci Winarti; Dian Purnamasari (Fakultas Hukum Universitas Trisakti, 2023)
Many people who work in the food industry exchange items like expired foods that are unfit for sale. the formulation of the issue surrounding the potential sanctions for the sale of expired food items at Hj. Asni's Assorted Spice Shop and the enforcement of a ruling in the case by the panel of judges at both the initial and appellate levels. Secondary and primary data are mentioned as a complement to the normative research-based research methodology. The research is descriptive in nature and uses the deductive approach to generate findings. The findings of the study and debate, namely the action of putting out-of-date food from the box onto the shelf, by a former employee of Hj. Asni, although Hj. Asni has given directions so that the product is suitable and has an expiry date separated, so in conclusion, Hj. Asni is still being held accountable for the negligence in monitoring the expired food products under his supervision (product liability) as well as the consideration of the Panel of Judges at the Jayapura District Court in the case of Hj. Asni in Decision Number 77/Pid.Sus/2017/PN.Jap is appropriate where the provisions of Article 8 paragraph (3) UUPK are cumulative and all elements must be proven, while the cassation decision granting the cassation request is only to fulfill a sense of justice and provide legal certainty considering this act is a repeated act.